Coaching ontológico: uma contribuição à gestão hospitalar - Moraes, Marilda Schiller de (2015)
This study s main goal is to identify how the use of Ontological Coaching, based on the Ontology of Language, can facilitate communication and assist in building healthy and productive environments within companies. In the universe of organizations the communication issue has great importance, because it is through the instructions and exchange of informations that are developed all the actions needed for the effectuation of processes, and respective development of products. So, we inhabit a linguistic world, in which the word, in special the spoken word, becomes the instrument by excellence of the executive s action, the essencial way to get in touch with others and to obtain results. Nonetheless, the administrative language, featured by short, direct, and many times urgent commands, tends to complicate the communication inside the companies. Assuming that a reflexive posture allows comprehension to deep personal transformations and that the realization of sensitization workshops may facilitate the processes of communication, motivation and leadership, transforming people into enabling vectors for the generation of a productive and wholesome environment in the organization, it was done a research with 141 professionals of the Hospital das Clínicas of Campo Limpo Paulista (HCCLP). Taking into account the main goal of the study, meetings of Ontogical Coaching took place, with 7 professionals responsible for the management of the referred institution, along with sensitization workshops, about Human Dynamics and Conversational Skills, for the 141 professionals allocated in the sectors of Reception and Nursing of the HCCLP. To enable the comparison of observable behaviours, there were developed two researches with quantitave approaches and two researches with qualitative approaches, based on Survey interviews, before and after the interventions, which made possible the mapping of the effectiveness of the use of sensitization methodology and the contribution of Ontological Coaching to Hospital Management. The results of the quantitative research indicated a growth of 0,4% in the perception of Communication between the sections of the institution, reflecting on a growth of 3,0% on the perception of employee s Motivation, despite the reduction of -0,7% in the perception of the teams on Leadership. Isolating of these percentuals the evaluation done by the employees from the management area, which went throught the Coaching, a significant improvement on Motivation, Communication and Leadership dimensions could be perceived, with positive evaluation percentuals of 17,5%, 17,1% and 14,5%, respectively, in the period comprehended between the two researches. In that same way, by evaluating the statements resultant of the qualitative research interviews, a lot of testimonials were observed claiming that the Coaching meetings and the workshops brought important contributions to the professionals holders of the management positions, along with the improvement in the communication between the teams allocated in the Reception and Nursing sectors. That being, the conclusion is that the exercise of the Ontological Coaching has a lot to contribute with Hospital Management